The Portuguese media system and the normative roles of the media: a comparative view - Santana-Pereira, J. (Análise Social, 2016)
This article analyzes the structure of the Portuguese media system and perceptions regarding the performance of its normative roles from a comparative perspective. This analysis allows us to determine if the patterns identified in the Portuguese case follow a common trend found in other western democracies as well as the structural constraints associated with performance differences. The empirical data analyzed show that the Portuguese media system is characterized by structural patterns and normative roles identical to those of other polarized pluralist systems, and that in Europe media performances depend greatly on the levels of journalist professionalization.